Regulation of STIM1/Orai1-dependent Ca2+ signalling in platelets - Lang, Florian; Münzer, Patrick; Gawaz, Meinrad; Borst, Oliver (Thrombosis and Haemostasis, 2013)
Platelet secretion and aggregation as well as thrombus formation of blood platelets critically depend on increase of cytosolic Ca2+ concentration ([Ca2+]i) mainly resulting from intracellular Ca2+ release followed by store operated Ca2+ entry (SOCE) through Ca2+ release activated channels (CRAC). SOCE is in part accomplished by the pore forming unit Orai and its regulator stromal interaction molecule (STIM). Orai1 and STIM1 transcription is stimulated by NFkB (nuclear factor kappa B). Serum- and glucocorticoid-inducible kinase 1 (SGK1) up-regulates NFkB-activity in megakaryocytes and thus Orai1- expression and SOCE in platelets. SGK1 is thus a powerful regulator of platelet Ca2+-signalling and thrombus formation and presumably participates in the regulation of platelet activation by a variety of hormones as well as clinical conditions (e.g. type 2 diabetes or metabolic syndrome) associated with platelet hyperaggregability and increased risk of thromboocclusive events. SOCE in platelets is further regulated by scaffolding protein Homer and chaperone protein cyclophilin A (CyPA). Additional potential regulators of Orai1/STIM1 and thus SOCE in platelets include AMP activated kinase (AMPK), protein kinase A (PKA), reactive oxygen species, lipid rafts, pH and mitochondrial Ca2+ buffering. Future studies are required defining the significance of those mechanisms for platelet Orai1 abundance and function, for SOCE into platelets and for platelet function in cardiovascular diseases.
Keywords: Platelet physiologypolymorphisms; kinases; signal transduction; Ca2+ (arterial thrombosis)